High incidence of cassava common mosaic virus in cassava plants and complete genome sequence of a distinct isolate from Brazil - Watanabe, Luís Fernando Maranho [UNESP]; Ribeiro-Junior, Marcos Roberto [UNESP]; Portilho, Angélica Maria Nogueira [UNESP]; Marubayashi, Julio Massaharu [UNESP]; Barreto da Silva, Felipe; Uzan, Juliana [UNESP]; Favara, Gabriel Madoglio [UNESP]; Krause-Sakate, Renate [UNESP] (My University, 2024)
The cassava common mosaic virus (CMV) is a pathogen that affects cassava plants. The complete genome sequence of a CsCMV isolate was obtained from cassava plants in São Paulo state, Brazil. Subsequent field surveys across multiple counties revealed a high prevalence of CsCMV, ranging from 67 to 100%. Phylogenetic analysis demonstrated two distinct genetic groups of CsCMV isolates in São Paulo, with the Brazilian isolate closely related to isolates from the United States and China. Considering that cassava is propagated vegetatively, the high incidence of CsCMV highlights the need to establish programs to obtain virus-free propagation materials.
Keywords: Cassava; Epidemiology; Genetic diversity; Re-emerging virus